From Public Participation to Co-Creation in the Cultural Heritage Management Decision-Making Process - Grcheva, Olgica; Oktay Vehbi, Beser (Mdpi, 2021)
According to the ongoing discussions of researchers, practitioners, and international legislation, the prioritization of top-down decision-making processes in public participation is questionable due to their ambiguous outcomes in various contexts associated with the management of cultural heritage. The main aim of this paper is to highlight and identify co-creation as a sustainable and significant bottom-up methodology that has a wide range of applications, especially in the domain of Cultural Heritage Management (CHM). It is presented as an alternative to the already existing, less democratic, and passive public participation decision-making processes. Examining the evolution of the terms and the processes, together with the common aspects and differences between public participation and co-creation is another goal of this paper. Based on these aims and goals, after conducting case study analyses in various contexts and comprehensive theoretical reviews of the international charters and ongoing practices associated with both key terms, public participation and co-creation, this paper introduces results that have the potential to solve the existing problems in public participation models and frameworks and successfully integrate communities into the CHM decision-making process through the implementation of the co-creation methodology.
Keywords: public participation; co-creative methodology; cultural heritage management; sustainable decision making; bottom-up approaches